KEYAKINAN-KEYAKINAN UTAMA MAHASISWA MEMILIH MATA KULIAH KONSENTRASI AKUNTANSI SYARIAH: STUDI ELISITASI BERDASARKAN THEORY OF PLANNED BEHAVIOUR - Darmawan, Yanto (Akuntansi Krida Wacana, 2018)
According to Theory of Planned Behaviour (TPB), intention is a result of attitudes toward behavior, subjective norms, and perceived behavioral control. TPB assumes that these components are determined by salient beliefs for each component. However, the determination of salient beliefs using elicitation studies received less attention from researchers. This study elicit students’ salient beliefs in relation to choose sharia accounting courses. 15 students who have attended sharia accounting courses completed questionnaires with eight open-ended questions eliciting beliefs concerning choose sharia accounting. The results of this study indicate that the most frequently mentioned salient beliefs related to behavioral beliefs are job opportunities, knowing Islamic law in accounting, teaching and learning atmosphere, the existence of practicum and sharia banking. Meanwhile, those related to normative beliefs are parents, family, friends, lecturers and those associated with control believe are computer applications, reference books, lecture materials, lecturer performance outside the classroom. The result of this elicitation study could be used to construct a full TPB questionnaire to investigate students’ intention to choose the course of sharia acounting.Keywords: elicitation study, sharia accounting, Theory of Planned Behaviour, TPB questionnaire